FEATURES OF THE FORMATION OF THE MODERN INFORMATIO IMAGE OF THE CRIMEA - Швец, А.Б.; Кузубский, В.А.; Вольхин, Д.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article highlights the specific study of information image of the territory. On the example of the recreational image of the Crimea examines strategy of television media in Ukraine and the Russian Federation in the formation image of region. Formulated the main trends of the regional strategy for the formation of a positive image of the Crimea.